2022
DOI: 10.2196/26276
|View full text |Cite
|
Sign up to set email alerts
|

Facial and Vocal Markers of Schizophrenia Measured Using Remote Smartphone Assessments: Observational Study

Abstract: Background Machine learning–based facial and vocal measurements have demonstrated relationships with schizophrenia diagnosis and severity. Demonstrating utility and validity of remote and automated assessments conducted outside of controlled experimental or clinical settings can facilitate scaling such measurement tools to aid in risk assessment and tracking of treatment response in populations that are difficult to engage. Objective This study aimed to… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 65 publications
(64 reference statements)
0
17
0
Order By: Relevance
“…[4] The latest type of information unfairness comes from Application Programming Interface(API) ambush that works on both algorithms, information/data, and substantiate outcomes. [5] This type of work helps us to understand how different types of information, ideas and characteristics of social media information/data can be largely considered and authenticated and in what way can be in touch arbitration mechanisms can be drafted to control pessimistic consequences.…”
Section: Social Media Platforms Used In 2022mentioning
confidence: 99%
“…[4] The latest type of information unfairness comes from Application Programming Interface(API) ambush that works on both algorithms, information/data, and substantiate outcomes. [5] This type of work helps us to understand how different types of information, ideas and characteristics of social media information/data can be largely considered and authenticated and in what way can be in touch arbitration mechanisms can be drafted to control pessimistic consequences.…”
Section: Social Media Platforms Used In 2022mentioning
confidence: 99%
“… 169 Posture head pitch variance, upper body movements reduced head movement in schizophrenia Abbas et al. 191 higher head movement in ASD de Belen et al. 192 Language Grandiosity unrealistic sense of superiority increased in bipolar Castro et al.…”
Section: Ml-powered Technologies For Psychiatrymentioning
confidence: 99%
“…As an example, research effort has been dedicated to using computer vision and voice to directly quantify motor activity. Some recent work has demonstrated that digital phenotyping parameters that reflect gross motor activity including speech characteristics (rate of speech, tone) and facial/head movements are associated with suicidal risk, 189 SSRI response in MDD, 251 negative symptomatology in schizophrenia, 191 and Parkinsonian tremor. 252 Such approaches are now being commercialized for all phases of drug development from proof of concept to direct measurement in order to make decisions about ongoing treatment needs.…”
Section: Ml-powered Technologies For Psychiatrymentioning
confidence: 99%
“…As an example, research effort has been dedicated to using computer vision and voice to directly quantify motor activity. Some recent work has demonstrated that digital phenotyping parameters that reflect gross motor activity including speech characteristics (rate of speech, tone) and facial/head movements are associated with suicidal risk [241], SSRI response in major depressive disorder [242], negative symptomatology in schizophrenia [243], and Parkinsonian tremor [244]. Such approaches are now being commercialized for all phases of drug development from proof-ofconcept to direct measurement to make decisions about ongoing treatment needs.…”
Section: Commercial and Research Platforms And Servicesmentioning
confidence: 99%